A policy review of Strategy 2022 – 2025, Culture Ireland - O'Brien, Maria (Irish Journal of Arts Management and Cultural Policy, 2022)
Culture Ireland is the government agency which supports the promotion of Irish arts worldwide. The aim of this policy review is primarily to identify key concepts in the recently launched revision of Culture Ireland’s strategy (Strategy 2022-2025) and to place them in the wider context of the role of arts and culture in Ireland. In particular, it highlights the implicit and explicit framing of arts policy as a way of operationalising Ireland’s culture on the global stage as a form of soft power.